Peningkatan Kualitas Batu Bata dengan Menggunakan Metode Taguchi pada UKM Batu Bata XYZ - Anggi Anggi; Eddy Eddy; Farida Ariani (Universitas Harapan Medan, 2021)
The large number of brick producers in the Batu Lapan Lubuk Pakam area, Deli Serdang, as well as market competition from manufacturers who use modern machines to produce bricks have made one brick producer who still uses traditional methods of manufacture compete to improve quality brick. To obtain good quality bricks, namely by looking at the compressive strength of the bricks produced, it is necessary to have an optimal raw material composition that can be produced through experimental designs. In this study, the experimental design used was the Taguchi method. The purpose of this study was to determine the factors that influence the quality of the bricks, to know the composition of the raw materials so that the optimal quality of the bricks was obtained, to know the usefulness of the Taguchi loss function to reduce production cost losses. From the identification of controlled factors, it is obtained the factors that influence the compressive strength of the bricks, namely the composition of the material, the time of stirring, the drying time and the burning time. Experiments were carried out with four different levels of factors. From the analysis, the optimal factor level combination is factor A level 1: clay composition 50%, factor B level 2: stirring time 4 hours, factor C level 1: drying time of 1 day and factor C level 2: burning time 3 days while the Taguchi loss function is sufficient to reduce production cost losses. The test results from 200 units of bricks showed a decrease in the percentage of brick defects from 6%-7,32% to 2,5%-3%.